2012
DOI: 10.1080/17480930.2012.679860
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship and growth of Typha latifolia L. across a NaCl gradient: a greenhouse study

Abstract: Oil sands surface mining operations in northeastern Alberta have created a substantial area of land needing to be reclaimed. Historically, these lands were a mosaic of uplands and boreal wetlands, particularly peatlands. While protocols for upland reclamation are well-defined, protocols for peatland reclamation are still in development. Two major concerns for peatland reclamations are (1) the ability of wetland plants to tolerate the increased sodicity present after surface mining and (2) the potential for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Comparatively, C. atherodes showed reduced performance in most attributes above 789 mg Na + L −1 , with significant differences manifested at a treatment of 1407 mg Na + L −1 . In similar trials, Koropchak and Vitt [ 39 ] found decreased survivorship and biomass of T. latifolia at 600 mg Na + L −1 , while Glaeser et al [ 40 ] found decreased performances and biomass of Beckmannia syzigachne after 850 mg Na + L −1 . The higher tolerances of both species of Carex indicate that these two species may provide the key ingredients to the vegetative recovery of oil sands sites with brackish waters.…”
Section: Discussionmentioning
confidence: 96%
“…Comparatively, C. atherodes showed reduced performance in most attributes above 789 mg Na + L −1 , with significant differences manifested at a treatment of 1407 mg Na + L −1 . In similar trials, Koropchak and Vitt [ 39 ] found decreased survivorship and biomass of T. latifolia at 600 mg Na + L −1 , while Glaeser et al [ 40 ] found decreased performances and biomass of Beckmannia syzigachne after 850 mg Na + L −1 . The higher tolerances of both species of Carex indicate that these two species may provide the key ingredients to the vegetative recovery of oil sands sites with brackish waters.…”
Section: Discussionmentioning
confidence: 96%
“…It is most commonly observed where the water depth is 0–32 cm above the soil surface, but is tolerant of water up to 1 m deep (Bansal et al, 2019; Grace, 1989). It is not desirable for fen reclamation because it is not peat‐forming, readily colonizes disturbed inundated areas, and grows in dense, tall monocultures that exclude other species (Bansal et al, 2019; Koropchak & Vitt, 2013; Wilcox et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast of halophytic biotypes as reported that biotypes of T. latifolia has the ability of growing well at salinity levels of 2.4% with a survival rate of 94%(Jesus et al 2014). Its survival rate was 56% if treated with 2400 mg L −1 of NaCl when growing in a greenhouse(Koropchak and Vitt 2013). Yet, T. latifolia can unlike T. glauca grow in acidic soil(Hotchkiss and Dozier 1949).Table-4.…”
mentioning
confidence: 99%